2022
DOI: 10.21203/rs.3.rs-1296403/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of Starch Synthase IIIa changes starch molecular structure and granule morphology in grains of hexaploid bread wheat

Abstract: Starch Synthase III plays a key role in starch biosynthesis and is highly expressed in developing wheat grains. To understand the contribution of SSIII to starch and grain properties, we developed wheat ssIIIa mutants in the elite cultivar Cadenza using in silico TILLING in a mutagenized population. SSIIIa protein was undetectable by immunoblot analysis in triple ssIIIa mutants carrying mutations in each homoeologous copy of ssIIIa (A, B and D). Loss of SSIIIa in triple mutants led to significant changes in st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Chain-length distribution of debranched starch was analysed as described by Fahy and colleagues (Fahy B., Gonzalez O., Savva G.A., et al, 2022) using a mixture model where the distribution components were estimated using constrained values of degree of polymerisation (DP) previously described by Hanashiro et al 1996(Hanashiro, et al, 1996 and Vilaplana et al 2012(Vilaplana, et al, 2012. The mixdist (version 0.5-5) R package was used to estimate mixture models (Macdonald P. & Du J., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chain-length distribution of debranched starch was analysed as described by Fahy and colleagues (Fahy B., Gonzalez O., Savva G.A., et al, 2022) using a mixture model where the distribution components were estimated using constrained values of degree of polymerisation (DP) previously described by Hanashiro et al 1996(Hanashiro, et al, 1996 and Vilaplana et al 2012(Vilaplana, et al, 2012. The mixdist (version 0.5-5) R package was used to estimate mixture models (Macdonald P. & Du J., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Starch isolated from sbeII and WT wheat flour was used to determine starch chain length distribution by size exclusion chromatography (SEC). Starch was isolated as described in (Corrado M., et al, 2020) and debranched using iso-amylase prior to analysis by HPLC-SEC as described by Fahy et al . 2022 (Fahy B., et al 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, breeding for wheat with less digestible starch is an important strategy to develop healthier staple foods. So far, reverse genetic studies in wheat have demonstrated potential for increasing resistant starch levels using induced mutations in starch biosynthesis genes (Botticella et al, 2018, Schonhofen et al, 2017, Hazard et al, 2015, Fahy et al, 2022). However, initial analyses of some mutants have shown detrimental effects on yield and on pasta and bread-making quality, thus identifying additional sources of genetic variation for starch digestibility could support the development of improved traits for commercial breeding applications (Schonhofen et al, 2017, Hazard et al, 2015).…”
Section: Introductionmentioning
confidence: 99%